2022
DOI: 10.1039/d2fo01934e
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide riboside ameliorates high-fructose-induced lipid metabolism disorder in mice via improving FGF21 resistance in the liver and white adipose tissue

Abstract: NR supplementation could ameliorate high-fructose-induced lipid metabolism disorder by improving FGF21 resistance in the liver and WAT, which may be related to the inflammation state mediated by SIRT1/NF-κB signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Existing studies have demonstrated that the NF-κB pathway can regulate lipid metabolism and then affect DSS-induced colitis [34], atherosclerosis [35] and NAFLD [36]. The latest research has disclosed that nicotinamide riboside ameliorate high-fructose-induced lipid metabolism disorder may be related to the regulation of inflammation mediated by the SIRT1/NF-κB signaling pathway [37]. AMPK is also identified as a key molecule in the regulation of biological energy metabolism and lipid metabolic-related diseases [38].…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have demonstrated that the NF-κB pathway can regulate lipid metabolism and then affect DSS-induced colitis [34], atherosclerosis [35] and NAFLD [36]. The latest research has disclosed that nicotinamide riboside ameliorate high-fructose-induced lipid metabolism disorder may be related to the regulation of inflammation mediated by the SIRT1/NF-κB signaling pathway [37]. AMPK is also identified as a key molecule in the regulation of biological energy metabolism and lipid metabolic-related diseases [38].…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was carried out as described in previous studies, , with slight modifications. Briefly, the liver tissues from different groups were homogenized on ice and centrifuged at low temperature, followed by collecting the supernatant and determining the protein concentrations by BCA assay (Meilunbio Biotechnology, China).…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting followed our previous procedures [ 26 , 27 , 28 ]. For nuclear extraction, placental whole lysates were suspended in a hypotonic buffer and stored on ice for 15 min.…”
Section: Methodsmentioning
confidence: 99%